Conceptualisation of an ethical risk assessment for higher education institutions - Grobler, A.; Horne, A.L. (South African Journal of Higher Education, 2017)
This article examines an ethical risk assessment conducted in one of South African largest higher education institutions. A statistical analysis of 1 687 respondents participating in the original ethical risk assessment survey was conducted. Confirmatory factor analyses supported a higher order, multidimensional model of three main factors, namely institutional ethical leadership orientation, individual/employee ethical orientation and institutional student-centeredness/orientation. Based on this examination and analysis this three-factor structure provides sufficient evidence of a conceptual ethical framework to be further tested empirically and used within higher education institutions.